COMMUNICATION STRATEGY IN AGRIBUSINESS EXTENSION (The Qualitative Study of Extension in The Partnership Context between Nucleus Estate and Smallholder) - MC Ninik Sri Rejeki (UPT Penerbitan Universitas Jember, 2012)
The dualistic culture reality is a primary characteristic of the agribusiness extension in the context of partnership between nucleus estate and smallhorder. The reality implies to the need of communication strategy in order to achieve the effectivity of the extension effort. Dualistic culture in estate system in Indonesia was started by dualistic economy, that is at one side big estate has orientation on modern capitalism and smallholder, on the other hand, has orientation on traditional pre-capitalism.The communication strategy covers two strategies. They are convergent strategy and divergent strategy. These strategies are used by agents of change from nucleus estate in their extension activities. This paper is based on qualitative study and takes partnership case at PT Pagilaran. PT Pagilaran is a company that moves on tea agribusiness and managed by Gadjah Mada university through Yayasan Pembina Fakultas Pertanian.